DAMPAK BENCANA ALAM BAGI SEKTOR PARIWISATA DI BALI - Ni Ketut Sutrisnawati (Institut Pariwisata dan Bisnis Internasional, 2018)
Natural disasters are natural phenomenon that can occur at any time anywhere. Natural disasters negatively affects society, either through damage to property or through loss of life, environmental damage, also affect various aspects of human life, such as economic, socio-cultural, security, etc. Tourism is an industry continues to be developed in many countries in the world. Tourism as a smokeless industry is strongly influenced by various aspects, one of which is security. Disaster as part of security has a huge influence on the tourism sector. Humans feel anxious and worried about visiting destinations that are prone to disasters. It cannot be denied that Bali is highly dependent on the tourism sector. The Mount Agung eruption in 2017, which lasted until 2018, had an impact on most Balinese people, especially those working in the tourism sector. Reduced tourist arrival due to travel warnings, as well as the closure of Ngurah Rai airport for several days due to volcanic ash bursts had caused the industry in the tourism sector to experience a downturn. To reduce the impact of natural disasters, especially on the tourism sector, various efforts and cooperation from all stakeholders are needed to jointly find solutions to solve the problems arising from this disaster. This solution can be in the form of prevention / pre-disaster, preparedness and post-disaster /recovery. With the existence of concrete efforts and actions before, during and after a disaster, it is expected to create a positive image of Bali so as to create sustainable tourism without worrying for natural disasters.Â Keywords: Natural Disasters, Tourism Sector, BaliÂ